The Restoration of Gregorian Chant: Solesmes & the Vatican Edition - Combe, Dom Pierre (Washington, DC Catholic University of America Press, 2003)
This book presents for the first time in English the fully documented history of the restoration of Gregorian chant, the Catholic Church's very own music.
Keywords: Abbaye Saint-Pierre de Solesmes (Sarthe, France); 19th Century (1801-1900); Plainchant